2022
DOI: 10.1049/gtd2.12461
|View full text |Cite
|
Sign up to set email alerts
|

An equilibrium‐based model to investigate market performance of power‐based electricity market

Abstract: The conventional model of the day-ahead electricity markets employs an energy-based approach to manage the competition among the players. Under this format, it is assumed that everything (including the demand and output power of the generating units) is constant during each hour. This assumption greatly simplifies the market, and it is widely incorporated over the globe. However, it leads to mismatches in the real-time operation. With the increase in the share of intermittent sources, such mismatches get highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Consequently, energy-based modelling has been claimed to induce mismatches between the day-ahead schedules and real-time operation. Power-based modelling, on the other hand, applies a trajectorial load curve, and this model has been proposed as a more promising approach as the technical limitations of the units can be considered more realistically, and the day-ahead schedules can be ensured to be consistent with the ramping capability of the generating units [80]. It is argued in Ref.…”
Section: Power-based Modelling Instead Of Energy-basedmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, energy-based modelling has been claimed to induce mismatches between the day-ahead schedules and real-time operation. Power-based modelling, on the other hand, applies a trajectorial load curve, and this model has been proposed as a more promising approach as the technical limitations of the units can be considered more realistically, and the day-ahead schedules can be ensured to be consistent with the ramping capability of the generating units [80]. It is argued in Ref.…”
Section: Power-based Modelling Instead Of Energy-basedmentioning
confidence: 99%
“…Rahmati and Akbari Froud [80] investigated the change in the electricity market design from energy-based modelling to power-based modelling. Their study confirmed the results of previous similar studies that an energy-based model may lead to real-time inconsistencies when the scheduling of the generators is infeasible.…”
Section: Power-based Modelling Instead Of Energy-basedmentioning
confidence: 99%